Simulation Study on Grounding Rod Using COMSOL Software - Abd Haris, Mohamad Adam; Othman , Nordiana Azlin (Evolution in Electrical and Electronic Engineering, 2023)
This paper presents a simulation-based study that focuses on three key factors: rod length, rod orientation, and soil resistivity, aiming to enhance knowledge of their impact on electrical parameters. Simulation works using COMSOL Multiphysics provide valuable insights into the relationship between these variables, aiding in the design and analysis of electrical systems and grounding installations. The simulation setup involves a conducting rod embedded in a heterogeneous soil model. The rod length is systematically varied at 1.5m, 3m, and 4.5m; while the rod diameter is maintained at 35mm; whereas soil resistivity and material properties are constant. By observing the potential voltage across the rod while changing its length, a nonlinear relationship is revealed. Additionally, the simulation explores the effect of rod orientation on current density distribution. Altering the angle of the rod concerning the ground surface allows for mapping the current density, demonstrating the influence of rod orientation on current flow. Moreover, the simulation incorporates variations in soil resistivity to analyze their impact on the electric field. Assigning different resistivity values to distinct soil regions enables the visualization of electric field distribution. Implementing this knowledge supports the design of efficient electrical systems, ensuring proper grounding and enhancing overall system performance. In conclusion, the selection of a 4.5m horizontal rod for the grounding system demonstrates careful consideration of safety and current distribution. This approach indicates an astute knowledge of the benefits of horizontal designs in limiting the dangers associated with localized hotspots and uneven current flows.